Mitral Valve Repair - Irbaz Hameed, MD; Adham Ahmed, BS; Christina Waldron, BS; Percy T. Algarate, MD; Michal Kawczynski, MD; Maurish Fatima, MBBS, BS; Amnah Alhazmi, MBBS; Samantha Colon, BS; Alexandria Brackett, MA, MLIS; Samuel Heuts, MD, PhD; Peyman Sardari Nia, MD, PhD; Mario Gaudino, MD, PhD; et al. (JACC: Advances)
Background: Despite strong recommendations from multiple societies to pursue durable mitral valve repair (MVr), repair rates and outcomes remain inconsistent across the world. This is partly due to limited surgeon and center experience and lack of centralization of care for this technically challenging operation. Objectives: The authors evaluate the association between annual case volume and contemporary long-term outcomes of patients undergoing isolated MVr. Methods: A systematic literature search was performed to identify contemporary studies on isolated MVr in adults from January 2013 to November 2023. The primary outcomes were long-term survival, freedom from reoperation, and freedom from recurrent mitral regurgitation (moderate-severe). A novel meta-analytic volume-outcome approach using reconstructed Kaplan-Meier-derived individual patient data from the original studies was used. A frailty Cox model was applied to study volume-outcome relationships. Studies were pooled for each reported outcome and divided into 3 tertiles (T1-3) based on the annual case volume and number of patients of each center. Results: A total of 14,070 patients from 60 studies were pooled. Sixteen studies (6,099 patients) reported long-term survival. The overall pooled 10-year survival was 70.8% (95% CI: 68.9%-72.8%). Compared to lower volume centers, centers performing >38 cases/y were associated with significantly improved long-term survival (HR: 0.42; 95% CI: 0.36-0.49; P < 0.001). For degenerative mitral valve disease, a volume cutoff of >45 cases/y was associated with significantly improved long-term survival (HR: 0.40; 95% CI: 0.32-0.49; P < 0.001). Twelve studies (4,230 patients) reported long-term freedom from reoperation and 10 studies (2,470 patients) reported Kaplan-Meier-derived long-term freedom from recurrent mitral regurgitation data, respectively. The overall pooled 10-year freedom from reoperation was 90.2% (95% CI: 88.1%-92.4%), while the overall pooled 10-year freedom from recurrent mitral regurgitation was 72.7% (95% CI: 68.9%-76.8%). Centers performing >45 cases/y (HR: 0.61; 95% CI: 0.44-0.84; P = 0.003) and >70 cases/y (HR: 0.64; 95% CI: 0.42-0.98; P = 0.042) were associated with significantly improved long-term freedom from recurrent mitral regurgitation and freedom from reoperation, respectively. For degenerative mitral disease, >45 cases/y was associated with significantly improved freedom from recurrent mitral regurgitation (HR: 0.51; 95% CI: 0.36-0.72; P < 0.001); the volume outcome association for freedom from reoperation was not statistically significant (P = 0.58). Conclusions: Our study validates volume cutoffs associated with optimal long-term outcomes following isolated MVr. We found MVr volumes of >38 cases/y, 45 cases/y, and >70 cases/y to be associated with significantly improved long-term survival, durability of repair, and freedom from reoperation, respectively. These findings may define experienced centers and surgeons for patients requiring MVr for primary/degenerative mitral valve disease.